Process-Aware Systems : First International Workshop, PAS 2014, Shanghai, China, October 17, 2014. Proceedings - Cao, Jian.; Wen, Lijie; Liu, Xiao.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2015)
This book constitutes the refereed proceedings of the First International Workshop on Process-Aware Systems, PAS 2014, held in Shanghai, China, in October 2014. The 5 revised full papers and 3 short papers were carefully reviewed and selected from 14 submissions. The papers are organized in topical sections on process modeling and comparison; workflow scheduling and resource allocation; scientific workflow verification; workflow applications.
Process modeling and comparison -- Workflow scheduling and resource allocation -- Scientific workflow verification -- Workflow applications.
Keywords: Information technology; Information storage and retrieva; Software engineering; Information Systems Applications (incl. Internet).; IT in Business; Information Storage and Retrieval; Software Engineering